Productive performance of winter cereals in an integrated system with pecan nuts (Research, Society and Development, 2024)
Integrated production systems, such as agroforestry, are important alternatives for optimizing land use, diversifying production, and improving the profitability of growers, but their success depends on studies to identify the most suitable species interactions. This work aimed to verify the performance of winter cereals (wheat and rye) for grain production in an agroforestry integration system with pecan trees (Carya illinoinensis). The experiment was conducted in the municipality of Encruzilhada do Sul – RS, in the years 2022 and 2023. The cultivars Tbio Trunfo (wheat) and BRS Serrano (rye) were used. The experimental design used was randomized blocks, with 6 replications. Pecan tree growth parameters (trunk diameter and height) and wheat and rye productivity were evaluated. From what was explored, it was observed that winter crops compared to the control provided a significant increase in the trunk-cross-sectional area of the pecan trees. Furthermore, the wheat crop had higher productivity than the rye crop, under the conditions evaluated. The results show that the production of winter cereals in integration with pecan trees is possible and can become an important alternative for diversifying production matrices, although future studies are necessary to determine the best cultivars and management to maximize the results obtained.